Elaboração e implantação do sistema de análise de perigos e pontos críticos de controle no processamento de leite pasteurizado tipo A - Tobias, Wanderleia [UNESP]; Giglio Ponsano, Elisa Helena [UNESP]; Pinto, Marcos Franke [UNESP] (Univ Federal Santa Maria, 2014)
Hazard analysis and critical control points (HACCP) is one of the main tools currently used to ensure safety, quality and integrity of foods. So, the aim of this study was to develop and implement the HACCP program in the processing of pasteurized grade A milk Checklists were used to assess on the level of the pre requisites programs and on the sanitary classification of the dairy industry and the results were used as references for the development of the HACCP system. A "decision tree" protocol was used for the identification of the critical control points (CCP). No physical or chemical CCP were identified, whereas pasteurization and packaging were considered biological CCP For these CCP, the limits for prevention, monitoring needs, corrective actions, critical limits and verification procedures were established. The pre requisites program was essential for the establishment of the system. The implementation of the HACCP for the processing of grade A pasteurized milk was efficient to control the biological hazards and enabled the product to comply with the legislation specifications and achieve safety.

A análise de perigos e pontos críticos de controle (APPCC) é uma das principais ferramentas utilizadas atualmente para a garantia da inocuidade, qualidade e integridade dos alimentos. O objetivo deste trabalho foi elaborar e implantar o sistema APPCC no processamento do leite tipo A pasteurizado. Por meio da aplicação de listas de verificação, foi avaliado o nível do programa de pré-requisitos e o panorama sanitário do estabelecimento, e o material gerado serviu de suporte para a implantação do sistema. O modelo de "árvore decisória" foi utilizado para a determinação dos Pontos Críticos de Controle (PCC), tendo sido identificados como PCC biológicos as etapas de pasteurização e envase e nenhum PCC químico ou físico. Para os PCC identificados, foram estabelecidas as medidas preventivas e corretivas, os limites críticos e os procedimentos de monitoramento e verificação. O programa de pré-requisitos foi fundamental para o estabelecimento do sistema. A implantação do plano APPCC no processamento do leite pasteurizado tipo A foi eficiente no controle dos perigos identificados e possibilitou ao produto atingir as especificações legais e alcançar a segurança.
Development and implementation of the hazard analysis and critical control points system for the processing of grade A pasteurized milk
Keywords: Food technology; Food safety; Food handling; Food legislation; Tecnologia de alimentos; Segurança alimentar sanitária; Manipulação de alimentos; Legislação sobre alimentos